Exit strategies for and potential alternatives to agricultural subsidy programs - Takeshima, Hiroyuki; Lee, Hak Lim (International Food Policy Research Institute, 2012)
Removing subsidies that have been applied to agricultural inputs and closing down subsidy programs, once introduced, have proved difficult to do in many countries, whether the subsidies are for irrigation1, seed2, or fertilizer.3 Long‐running subsidy programs inflate the fiscal burden that governments must manage. While it is important to assign long‐term goals to a subsidy program in their design so that the program promotes policy consistency, stability, and confidence in input markets for farmers and input traders, such long‐term goals also result in subsidy programs becoming politically entrenched. Such long‐running subsidy systems often result in fraud or diversion of subsidies to purposes for which the programs were not designed.4 From their beginning, subsidy programs should be designed with a clear and feasible exit strategy.